Micromobility integration guidelines proposal in Metropolitan Lima - Iturraran Zapata, Rodrigo (2023)
Micromobility, in Metropolitan Lima, has a lack of focus at the level of definition, classification and competencies, producing a normative and institutional gap, which does not allow an adequate management to the different public entities that govern it. In this article, as a result of the review of the different documents in force according to manuals, decrees, ordinances, among other publications corresponding to the three (03) levels of government, as well as international entities, four (04) aspects are identified as part of the diagnosis, referred to modal classification and categorization, infrastructure, regulation and institutional, and integrated. In view of this, the Integration of Micromobility in Metropolitan Lima Guidelines are proposed, which is composed of the Conceptualization and modal characterization, the Cataloging of infrastructure, and the Implementation of a digital platform for demand management. Similarly, management indicators and institutional strategies are proposed, establishing the main functions of the micromobility actors as part of a comprehensive approach.